Fiber optic interrogator based on colorimetry technique for in-situ nitrate detection in groundwater - Aulakh, Navneet Singh; Kaler, Rajinder Singh (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Nitrate poisoning occurs when nitrite is absorbed into the blood, where it changes the red-colored blood pigment, called hemoglobin, to methemoglobin. Hemoglobin carries oxygen from the lungs to the other tissues, but methemoglobin cannot carry oxygen. Poisoning occurs when the methemoglobin concentration in the blood stream is so high that the oxygen carrying capacity of the blood is reduced to a critical level. Over the years nitrate contamination has acquired alarming proportions due to seepage of nitrates of fertilizers into the soil. Though several methods of monitoring nitrate concentration have been devised with some success, there is still a persistent need for devising easily deployable and in-situ techniques for monitoring nitrates in groundwater. Fiber optic techniques are capable of meeting these requirements, besides offering several other important advantages. Fiber optic nitrate detection sensors have thus become quite attractive and are currently being investigated to address the high costs associated with the existing nitrate concentration monitoring procedures. This paper describes fiber optic interrogator for in-situ nitrate detection in groundwater based on colorimetry technique.
Optica Applicata, Vol. 38, 2008, nr 4, s. 727-735
Keywords: optyka; fiber optic sensors; nitrate concentration; groundwater; colorimetry